Survei Asupan Asam Folat dan Seng pada Ibu Hamil di Jawa Barat - Sri Rahayu; Lani Gumilang; Sri Astuti; Sefita Aryuti Nirmala; R. Tina Dewi Judistiani (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: The lack of folic acid and zinc intake has considerable impact on both mother and fetus, and based on this research, the intake of folic acid and zinc among pregnant women in West Java is still quite low.Objective: The purpose of this research was to know the intake and average of folic acid and zinc among pregnant women in West Java.Methods: The method of this research was descriptive using cross sectional research design, and the sample was selected by using total sampling method from research of Academic Leadership Grant (ALG) on all first trimester pregnant women as many as 176 respondents who lived in the city of Sukabumi, Cirebon, Bandung and Cimahi recruited in the period of July 2016 - February 2017. Data source was the secondary data from food diary. The analysis used univariate data.Results: Most of the respondents with the folic acid intake not fulfilled were 97,2% and most of them with the zinc intake not fulfilled were 96%, with the average of folic acid intake 163 μg/day and the average of zinc intake 5,1 mg/day.Conclusion: Most of the respondents are categorized in the not fulfilled folic acid and zinc intake with the average under the Recommended Dietary Allowances (RDA) for pregnant women.